Insight into regeneration mechanism with sulfuric acid for arsenic poisoned commercial SCR catalyst. Issue 1 (February 2020) - Tian, Yuanmeng; Yang, Jian; Liu, Lan; Liu, Qingcai; Kong, Bowen; Lin, Fan; Kong, Ming; Hu, Guang
Abstract: Washing method by sulfuric acid was investigated in the context of deactivation and regeneration mechanism of arsenic deactivated catalyst over V2 O5 -WO3 /TiO2 catalyst. The physical and chemical properties changes for catalysts were characterized by XRD, SEM, BET, Raman, XPS, NH3 -TPD and in situ DRIFT, therein including morphology, structure, chemical states, surface acidity and functional groups. The results indicated that arsenic species mainly consisted of As2 O5 on the arsenic poisoned catalyst surface. It increased N2 O formation due to high active oxygen ratio of poisoned catalyst. After regeneration, the N2 O formation was reduced. Arsenic oxides covering on catalyst surface could be almost wipe off with sulfuric acid. As-OH group disappeared, and the Brønsted and Lewis acid sites were re-exposed. Moreover, a new Brønsted acid sites (S-OH) was formed by chelating bidentate sulfates (SO4 2− ) since it introduced S=O into anatase TiO2 lattice. However, some vanadium species were lost and the remaining species tended to form V 4+, the activity had an apparent decrease in the temperature range of 300–400 °C. Graphical abstract: Image 1 Highlights: Arsenic oxides could be wipe off by sulfuric acid, including all As 3+ and most As 5+ species. It was found that SO4 2− introduced S=O into anatase TiO2 lattice of catalyst. A new Brønsted acid sites come from S-OH, which formed by S=O, do good to the promotion of SCR reaction.